2016
DOI: 10.1080/03009734.2016.1218575
|View full text |Cite
|
Sign up to set email alerts
|

Swedish parents’ interest in preconception genetic carrier screening

Abstract: IntroductionGenetic technologies advance rapidly. It is possible to undergo genetic carrier screening before pregnancy to examine genetic risks to future offspring. We aimed to investigate parents’ interest and motives towards preconception genetic carrier screening (PCS) as well as factors associated with interest in PCS.Material and methodsOur study sample consists of 777 parent couples within the longitudinal Swedish Pregnancy Planning study. Women responded to questionnaires at three occasions: in early pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…The CSER project with the highest rate of decline was the NextGen site at Kaiser Permanente, which was the only site performing GS for carrier status in healthy adults. Genetic professionals express high interest in offering expanded carrier screening (Lazarin et al 2016); however, uncertainty and concern about negative consequences have been cited by patients (Ekstrand Ragnar et al 2016;Schneider et al 2016). Thus, it is possible that offering GS in the context of reproductive planning could warrant unique considerations.…”
Section: Discussionmentioning
confidence: 99%
“…The CSER project with the highest rate of decline was the NextGen site at Kaiser Permanente, which was the only site performing GS for carrier status in healthy adults. Genetic professionals express high interest in offering expanded carrier screening (Lazarin et al 2016); however, uncertainty and concern about negative consequences have been cited by patients (Ekstrand Ragnar et al 2016;Schneider et al 2016). Thus, it is possible that offering GS in the context of reproductive planning could warrant unique considerations.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies that included individuals of reproductive age have found general interest in expanded carrier screening. 35,36 A survey of 777 Swedish parent couples 51 found that about one-third of couples were interested in preconception carrier screening, just under one-third were not, and the remainder were uncertain. The authors attributed the range of interest in part to relatively low knowledge of carrier screening, which was neither standard of care nor marketed to consumers in Sweden.…”
Section: Challenges For Expanded Carrier Screeningmentioning
confidence: 99%
“…On the other hand, a study by Gilmore et al in 2017 explored the patients' reasons for declining preconception ECS, which included time limitation, not wanting the information, and potential anxiety. In addition, some studies have indicated that the majority of patients are uncertain about if they would like ECS or not (Ekstrand Ragnar et al 2016;Plantinga et al 2016).…”
Section: Introductionmentioning
confidence: 99%